1993
DOI: 10.1161/01.atv.13.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated glucose on cyclic GMP and eicosanoids produced by porcine aortic endothelium.

Abstract: The short-term effects of elevated glucose on cyclic GMP (cGMP) and eicosanoid production in pig aortic endothelial cell monolayers was determined by incubating cells in 5.5 mM or 44 mM glucose for 6 hours. Bradykinin-or A23187-stimulated cGMP production was significantly reduced in cells incubated in 44 mM glucose compared with 5.5 mM glucose. Stimulation of cGMP levels with exogenously added nitric oxide (NO) was also decreased to a similar extent in cells exposed to 44 mM glucose. These data suggest that NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
1
5
1
Order By: Relevance
“…Since the plateau phase of ionomycin was not altered by glucose, this suggests a defect that is unique to receptor-mediated coupling of intracellular Ca 2+ release and extracellular Ca 2+ entry. As opposed to the findings of defective Ca 2+ i signalling and NO activity by elevated glucose exposure of bovine (this study), porcine [22,23] and rat [24] endothelial cells, other investigators have shown that elevated glucose exposure enhanced basal or agoniststimulated Ca 2+ i signalling in porcine [21] and human umbilical vein endothelial cells [32]. These discrepancies may arise from variances in culturing conditions and media, type of endothelial cells, glucose concentration and exposure time, and/or the conditions of measurement of Ca 2+ i and NO/cyclic GMP.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Since the plateau phase of ionomycin was not altered by glucose, this suggests a defect that is unique to receptor-mediated coupling of intracellular Ca 2+ release and extracellular Ca 2+ entry. As opposed to the findings of defective Ca 2+ i signalling and NO activity by elevated glucose exposure of bovine (this study), porcine [22,23] and rat [24] endothelial cells, other investigators have shown that elevated glucose exposure enhanced basal or agoniststimulated Ca 2+ i signalling in porcine [21] and human umbilical vein endothelial cells [32]. These discrepancies may arise from variances in culturing conditions and media, type of endothelial cells, glucose concentration and exposure time, and/or the conditions of measurement of Ca 2+ i and NO/cyclic GMP.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the restoration of bradykinin-stimulated [Ca i ] was associated with an improvement in NO activity as judged by the improved cyclic GMP generated in RFL-6 detector cells. This is consistent with a role of Ca Previous studies have shown that elevated glucose decreases agonist-stimulated Ca 2+ i production or NO activity or both in porcine [22,23] and rat endothelial cells [24]. Furthermore, previous exposure of endothelial cells to exogenous reactive oxygen (e. g. peroxides) also diminishes receptor-dependent Ca 2+ i signalling [25±27].…”
Section: Discussionsupporting
confidence: 84%
“…These studies suggest that there is an increase in the production of vasoconstrictor PGs in diabetic vascular tissue and vessels exposed to elevated glucose, which has been confirmed in radioimmunoassay studies [58]. Furthermore, cultured aortic endothelial cells exposed to elevated glucose produce increased quantities of PGs, such as PGF 2α [59]. These findings indicate that in diabetic conduit vessels, PGs lead to significant vascular dysfunction and may be responsible for the altered smooth muscle reactivity seen under these conditions.…”
Section: Pathophysiological Effects Of Prostanoids On Corporal Smoothmentioning
confidence: 61%
“…In the rat aorta of experimental diabetes, decreased functional NO activity, a diminished response to endothelium-dependent vasodilators and an unchanged response to endothelium-independent vasodilators has been observed [106]. In porcine aortic endothelium, hyperglycaemia has been shown to directly inhibit NO synthase and reduce endothelial cell guanylate cyclase activity [107].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%